(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Domestic workers who are women are not entitled to the same job security as employees in offices, schools, and other establishments. Women who work as domestic help therefore lack job security because their employment is dependent on the whims and fancies of their employers. The mood of employers will once more influence a pay increase for female domestic workers. Many female domestic workers have been employed by the same employer for many years without receiving a pay increase. This article explores the socio- economic conditions of female domestic workers in Chennai city of Tamil Nadu. The survey was conducted between January and July of 2023. Both primary and secondary data were used to inform the study. The researcher used non-probability sampling and a convenient sampling method to collect the sample because the population of Chennai City was initially divided into fifteen zones. In Chennai, Tamil Nadu, 150 domestic workers were chosen as respondents. With the aid of a schedule, 150 domestic workers in Chennai City provided information about the socioeconomic status of the respondents.